HUBUNGAN KUALITAS PELAYANAN DAN PENINGKATAN KETERAMPILAN SOSIAL WARGA BINAAN DI UPT REHABILITASI SOSIAL BINA KARYA DESA WARUNGDOWO KECAMATAN POHJENTREK KOTA PASURUAN - Permana, Aditya Eka; Erwantiningsih, Eni; Wahyuni, Hari (Bhinneka Multidisiplin Journal, 2025)
Social rehabilitation is a systematic effort to restore and develop the abilities of individuals experiencing social dysfunction, including in terms of social skills, so they can reintegrate effectively into society. This study aims to determine the relationship between service quality and the improvement of social skills of inmates at the Bina Karya Social Rehabilitation Unit (UPT), Warungdowo Village, Pohjentrek District, Pasuruan City. Service quality is measured through five indicators: reliability, responsiveness, assurance, empathy, and physical evidence. Meanwhile, inmates' social skills are measured based on indicators: assertive communication, conflict resolution, empathy, and adaptive behavior in groups. The research method used is quantitative with a descriptive correlational approach. The sampling technique used purposive sampling with a total of 46 inmates as respondents. Determining the sample through special considerations, namely: Recommendations from the UPT, Health Workers, and Criteria Based on Independence in Activities. The results of the study showed a correlation coefficient (R) of 0.633 with a significance level of 0.000 (<0.05), indicating a strong and significant positive relationship between service quality and inmates' social skills. Therefore, the higher the quality of service provided, the higher the inmates' social skills.